Analysis of refracturing in horizontal wells: Insights from the poroelastic displacement discontinuity method. (24th April 2018) - Rezaei, Ali; Bornia, Giorgio; Rafiee, Mehdi; Soliman, Mohamed; Morse, Stephen
Summary: In this paper, a fully coupled 2‐dimensional poroelastic displacement discontinuity method is used to investigate the refracturing process in horizontal wells. One of the objectives of refracturing is to access new reserves by adding new hydraulic fractures in zones that were bypassed in the initial fracturing attempt. Pore pressure depletion in the vicinity of old fractures directly affects the state of stress and eventually the propagation of newly created hydraulic fractures. Thus, a poroelastic analysis is required to identify guidelines for the refracturing process, in particular to understand the extension of the pore pressure depletion, and eventually, the orientation of new as well as old fractures. We propose a fully coupled approach to model the whole process of child fracture propagation in a depleted area between 2 parent fractures in the same wellbore. This approach omits the need of using multistep workflow that is regularly used to model the process. The maximum tensile stress criterion ( σ criterion) is used for hydraulic fracture propagation. The proposed method is verified using available analytical solutions for total stress and pore pressure loading modes on a line fracture in drained and undrained conditions. Then, test cases of multifractured horizontal wells are studied to calculate the time evolution of the stress and pore pressure fields around old fractures and to understand the effect of these fields on the propagation path of newly created fractures. Finally, the effect of the pore pressure depletion on the propagation path of the newly created fractures in the bypassed area of the same wellbore is studied. The results show that the depleted areas around old fractures are highly affected by the extent and severity of the stress redistribution and pore pressure depletion. It is observed that a successful creation of new fractures may only happen in certain time frames. The results of this study provide new insights on the behavior of newly created fractures in depleted zones. They also clarify the relationship between stress change and pore pressure depletion in horizontal wells.